2021
DOI: 10.1002/ente.202100147
|View full text |Cite
|
Sign up to set email alerts
|

Binding Li3PO4 to Spinel LiNi0.5Mn1.5O4 via a Surface Co‐Containing Bridging Layer to Improve the Electrochemical Performance

Abstract: Coating the surface of cathode materials with Li3PO4 to improve the cycling performance is commonly practiced; however, obtaining an effective and uniform coating of Li3PO4 on cathode materials is extremely difficult due to the lack of strong bonds between them. Herein, this issue is solved by coating the surface of LiNi0.5Mn1.5O4 with Li3PO4 via a novel hydrothermal method. It is shown that a uniform Li3PO4 surface coating can only be obtained by introducing a small amount of additional metal ions, such as Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Nevertheless, the structural incompatibility between the rhombohedral Li 3 PO 4 and the material structures makes it difficult for rhombohedral Li 3 PO 4 to bond to the surface of the spinel cathode material making it difficult to combine them; these coating processes tend to form an uneven modification and poor crystallographic layer . Recently, Wu et al reported that the introduction of Co/Fe as a bridging ion in the process of spinel coating can effectively induce a uniform coating of structurally incompatible Li 3 PO 4 on the surface of the spinel cathode structure, exhibiting superior high-temperature capacity retention to that of the bare LMO electrode. , To study the reaction of the electrode/electrolyte interface, a pulsed laser deposition method was used to prepare Li 3 PO 4 epitaxial film-coated LMO, which effectively improved the electrode structure and surface stability and the electrochemical properties of the thin-film electrode. , Li et al suggest that using ball milling and high-temperature heating to coat the LiMn 2 O 4 surface with a nano-Li 3 PO 4 layer to improve the high-temperature performance of the materials, the electrode exhibited a 19.4% increase in capacity retention after 100 cycles at 55 °C . Previous works have suggested that if the coating material is loosely bonded with the cathode surface, the improvement in cycling performance is limited, especially at high-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the structural incompatibility between the rhombohedral Li 3 PO 4 and the material structures makes it difficult for rhombohedral Li 3 PO 4 to bond to the surface of the spinel cathode material making it difficult to combine them; these coating processes tend to form an uneven modification and poor crystallographic layer . Recently, Wu et al reported that the introduction of Co/Fe as a bridging ion in the process of spinel coating can effectively induce a uniform coating of structurally incompatible Li 3 PO 4 on the surface of the spinel cathode structure, exhibiting superior high-temperature capacity retention to that of the bare LMO electrode. , To study the reaction of the electrode/electrolyte interface, a pulsed laser deposition method was used to prepare Li 3 PO 4 epitaxial film-coated LMO, which effectively improved the electrode structure and surface stability and the electrochemical properties of the thin-film electrode. , Li et al suggest that using ball milling and high-temperature heating to coat the LiMn 2 O 4 surface with a nano-Li 3 PO 4 layer to improve the high-temperature performance of the materials, the electrode exhibited a 19.4% increase in capacity retention after 100 cycles at 55 °C . Previous works have suggested that if the coating material is loosely bonded with the cathode surface, the improvement in cycling performance is limited, especially at high-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%